Molecular and phenotypical characterization of Salmonella enterica isolated from humans in São Paulo State : Caracterização fenotípica e molecular de amostras de Salmonella enterica isoladas de humanos no Estado de São Paulo - Calarga, Aline Parolin, 1992- (2020)
Orientador: Marcelo Brocchi